Los trotskistas bajo el terror nazi Una historia de la IV Internacional durante la Segunda Guerra Mundial - Luparello, Velia (Ariadna Ediciones, 2021)
The study of the origins and early years of the Fourth International acquires a special relevance when considering them as part of the process of construction and criticism of the organizational and political tools of the working class that continues to this day. From its origins, the Fourth International was marked by political disputes within the Communist International, by the first positions as the Left Opposition, by the persecution of Trotskyist sympathizers and by the assassination of Leon Trotsky. Thus, this book is based on the need and the importance of investigating the history of Socialist Internationals in the key of an international history of socialism, insofar as the local and regional expressions of this current can be comprehensively understood through comparative and transnational analysis. Trotskyists under Nazi terror. A history of the Fourth International during World War II, develops a historical analysis of the political perspective carried out by the Fourth International in Europe during World War II through the comparative study of the French, North American, Belgian and British sections. Taking as one of the central axes the resurgence of the discussion on the national question in Europe, it is observed how the crisis of the Fourth International did not begin with the debate on entryism in 1953 but ten years before, due to the difficulties of the organization to adapt to the new European scenario inaugurated in mid-1943 with the deposition of Benito Mussolini and the beginning of the "bourgeois-democratic counterrevolution" from the intervention of the United States during the last years of the war.